Hubungan Kepadatan Bulu Babi (Echinoidea) dan Tutupan Terumbu Karang pada Kawasan Intertidal Pantai Sanur - Tiara Permata Sari; Abd. Rahman As-syakur; Yulianto Suteja; Dwi Budi Wiyanto (Journal of Marine and Aquatic Sciences, 2017)
Marine intertidal region is an area that is affected by the mainland. One of the ecosystems found in the intertidal area is the coral reef ecosystem. Urchin is one that lives on these ecosystems. Sanur Beach area has coral reefs and the intertidal zone is quite extensive. The many activities and cruise tourism in Sanur Beach will indirectly affect the life of coral reefs and associated animal in it in this case urchins. The purpose of this study was to determine the relationship density of sea urchins and coral reefs cover percentage in the intertidal area on Sanur Beach. Research done during low tide. Coral reef data collection method and the density of sea urchins using 5x5m quadratic transects were analyzed using Pear Person bivariate correlations. Urchin densities ranging between 0-2.04 ind/m2. The percentage cover coral reefs ranged from 0.1- 17.9%. High and low density of sea urchins and the percentage of coral reefs affected allegedly incompatibility place their lives and because of pressure from community activities in Sanur. The density of sea urchins and the percentage of coral cover has a significant relationship with a strong degree of correlation is 0.79. Positive direction on that relationship means that the higher percentage of coral reefs, the higher density of sea urchins. This assume in which they live almost the same that is in need of a hard substrate and urchins use of coral reefs as a shelter.